Conversão biotecnológica de casca de arroz em celulose bacteriana - Araujo, Raiara Boessio (2019)
The state of Rio Grande do Sul is the major national rice producer and generates each year large volumes of rice husk (RH) ̶ a left-over biomass with no controlled destination, composed essentially by lignin, cellulose and hemicellulose, and making up to 20% of the initial volume of the whole product. As a lignocellulosic biomass, RH can actually be converted in to biotechnological products with high added value, among them, bacterial cellulose (BC), a technological polymer with a plethora of applications (medical, food, material sciences). Aiming to yield BC, the pretreated RH (0,297 mm, washed) was submitted to alkaline hydrolysis using 6.5% NaOH solution w v-1, 35 min reaction and 80 °C. After this, a CCRD was set to verify which experiment would led to the highest concentration of fermentable sugars in hydrolysate. The experiments were carried out with dilute H2SO4 and HCl solutions, bring about as best condition 3.7% H2SO4 solution, 40 min reaction and 160 °C, ensuing a sugar production of 19,64 g glucose L-1. After that, the hydrolysate was treated by passing through activated carbon to eliminate interferers formed during the hydrolysis. The treated hydrolysate was then analyzed by HPLC-RID and concentrations up to 24.0 g glucose L-1 were obtained. This treated hydrolysate was used as fermentative medium for the production of CB by Gluconacetobacter hansenii (ATCC 23769). Preliminary tests using ozone as hydrolysate detoxificant indicate absence of sugar degradation during the ozonation, as well as no influence over the sugar consumption during the fermentation stage, which allows anticipating a good chance using it. Pronal®, yeast extract, ammonium sulfate and urea were tested as nitrogen sources (from 2 to 6 g L-1) and the best results obtained after a multivariate fermentation trial indicate the yeast extract and urea as the ultimate sources for bacterial cultivation. In the end stage of characterization of the extracted product, techniques such as FTIR, XRD and AFM were employed. Finally, a brief economic assessment was proposed; together with the good results obtained, it can summarized that RH can be looked as a viable biomass to be converted in CB ̶ fitting well within the contemporary biorefinery concept.